Mapping of hematite ore deposits using multi-sensor data in the Sekota District, Northern Ethiopia - Jerbaw Tiruneh Abejehu; Binyam Tesfaw Hailu; Worash Getaneh; Karuturi Venkata Suryabhagavan (Geosystems and Geoenvironment)
Iron plays a vital role in fueling the economic development and technological advancement of a country. Despite Ethiopia, being endowed with a large amount of iron ore resources in different parts of the country, prospective zones are not delineated properly. Therefore, this study aims to identify the iron ore prospective zones in the Sekota district of Ethiopia utilizing ASTER and Sentinel−2A satellite data for further onsite exploration and testing. In addition, powder diffraction analysis (XRD) was conducted to determine the dominant mineralogical phases. The image processing techniques such as ASTER band 2/band 1 (ASB2/B1) and Sentinel−2A band 4/band 2 (S2B4/B2) band ratios, principal component analysis (PCA), and subpixel level mapping technique, mixture-tuned matched filtering (MTMF) were used to map the distribution of hematite. ASB2/B1 and S2B4/B2 band ratios mapped hematite iron ore covering an area of 102.50 and 97. 68 km2. The selected PC4 of ASTER delineated hematite mineralized zones covering 133.40 km2 and Sentinel 2 PC3 of 110.70 km2 area. A very high spectral feature fit was found between the extracted hematite endmember and USGS resampled hematite spectra. The spectral fit of the endmember was 0.74 for ASTER and 0.86 for Sentinel−2. Hematite anomaly zones were identified with MTMF using these endmembers in different parts of the study area. Powder X-ray diffraction analysis (XRD) revealed high hematite phases ranging from 36.8%−85.5% of Fe2O3. A strong positive correlation was found between S2B4/B2 and S2B4/B2 (r = 0.83), ASB2/B1 and ASTER PC4 (r = 0.94). Moderate correlations for ASB2/B2, S2B4/B2 (r = 0.44), PCA (r = 0.44), ASTER and Sentinel−2 MTMF (r = 0.36). Results of both datasets show comparable areal coverage and overlay with three of the existing known iron occurrence polygons. Thus, it is evident that techniques employed are effective in narrowing hematite anomalies zones for further onsite gological exploration.